EVALUASI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PEMERINTAH DESA GUNUNGGEDE KECAMATAN WONOTIRTO KABUPATEN BLITAR - Eko Adi Susilo (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2019)
Based on the background of the problems described above, the authors formulated the problem in this study is how community satisfaction with public services in Gununggede Wonotirto Kabupaten Blitar. The purpose of this study was to find out how community satisfaction with public services in Gununggede Wonotirto Blitar. Based on the discussion described, it can be concluded that community satisfaction with public services in Gununggede Wonotirto Blitar is very good, and the community also felt very satisfied with the service provided by the office . Although the service can be said to be very good, but the services in Gununggede Wonotirto Blitar will continue to improve the quality of services to the village community by adding facilities and infrastructure so that the community feels comfortable and at home in Gununggede Office Wonotirto Blitar